2007
DOI: 10.1007/s11205-007-9117-3
|View full text |Cite
|
Sign up to set email alerts
|

Studying children in armed conflict: data production, social indicators and analysis

Abstract: Children, Armed conflict, Child soldiers, Living conditions,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…The limited age range was selected because children younger than seven years of age are seldom targeted for abduction, or are quickly released, so the age group selected for this study allowed for an examination of how prolonged abduction affects its youngest victims. The age range was also limited because previous research has indicated that older children and adolescents face a very distinct set of wartime risks from their younger counterparts (Pedersen & Sommerfelt, 2007). Further, in an effort to avoid conflating sets of experiences given the small sample size, only male narratives were considered as boys and girls abducted for use as child soldiers face risks particular to their gender (Pedersen & Sommerfelt, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The limited age range was selected because children younger than seven years of age are seldom targeted for abduction, or are quickly released, so the age group selected for this study allowed for an examination of how prolonged abduction affects its youngest victims. The age range was also limited because previous research has indicated that older children and adolescents face a very distinct set of wartime risks from their younger counterparts (Pedersen & Sommerfelt, 2007). Further, in an effort to avoid conflating sets of experiences given the small sample size, only male narratives were considered as boys and girls abducted for use as child soldiers face risks particular to their gender (Pedersen & Sommerfelt, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…The age range was also limited because previous research has indicated that older children and adolescents face a very distinct set of wartime risks from their younger counterparts (Pedersen & Sommerfelt, 2007). Further, in an effort to avoid conflating sets of experiences given the small sample size, only male narratives were considered as boys and girls abducted for use as child soldiers face risks particular to their gender (Pedersen & Sommerfelt, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…A child combatant/child soldier (interchangeably used in this article) is any child, boy or girl, under the age of 18 who is compulsorily, forcibly, or voluntarily recruited or otherwise used in hostilities by armed forces, paramilitaries, civil defense units, or other armed groups. Child soldiers are used for sexual services, as combatants, messengers, porters, or cooks (Pedersen and Sommerfelt 2007: 255). A Report of the United Nations Secretary General (2003) on ‘Children and Armed Conflict’ enlisted the Communist Party of Nepal-Maoist (CPN-M) as one of the parties recruiting children in their armed groups (Report of the United Nations Secretary General 2004: 121).…”
Section: Child Combatants Recruitment By the Maoists As A Human Rightmentioning
confidence: 99%
“…Some delimit their target population according to geography, type of trafficking, age and gender, for instance by looking at victims of trafficking among adult women in prostitution in Norway. As I have suggested elsewhere, another useful distinction can be made between the three different stages that a person can be in with regard to trafficking: persons at risk, current victims and former victims of trafficking (Pedersen and Sommerfelt, 2007;. While the two first are associated with severe problems for primary data collection, data production and analysis is more likely to be successful when we target the last group -the former victims.…”
Section: A Focus On Observable Populations and Behaviourmentioning
confidence: 99%